A study on service quality towards customer satisfaction: Eastern College of Kota Kinabalu Sabah region / Firdausiah Abdul Momen - Abdul Momen, Firdausiah (2014)
This study, researcher is aim to investigating the level of service quality of Eastern College of Kota Kinabalu Sabah Region towards customer satisfaction. Investigate the attribute of service quality and dimension that will contribute to reach the customer satisfaction. A conceptual model including four dimensions which are entitled teaching, academic staff, course structure and academic facilities, reputation and environment was represented for measuring service quality. The research finding suggest that in all four dimensions, there are academic staffs and teaching dimension has good level of service quality. The study shows how service quality of Eastern College of Kota Kinabalu satisfy students and recommend best strategic for Eastern College, in order to improve their service quality due to customer satisfaction.